2008
DOI: 10.1063/1.2975994
|View full text |Cite
|
Sign up to set email alerts
|

High brightness extreme ultraviolet (at 13.5 nm) emission from time-of-flight controlled discharges with coaxial fuel injection

Abstract: Articles you may be interested inOptimization of a gas discharge plasma source for extreme ultraviolet interference lithography at a wavelength of 11 nm

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…6 the theoretical spectra are compared to recent DPP results recorded with a microcapillary laser triggered discharge [21,22]. The electron density of the DPP is expected to be the order of 10 19 −10 20 cm -3 again comparable to that in a Nd:YAG plasma.…”
Section: Fig 6: Comparison Between a Discharge Produced Plasma (Dpp)mentioning
confidence: 93%
“…6 the theoretical spectra are compared to recent DPP results recorded with a microcapillary laser triggered discharge [21,22]. The electron density of the DPP is expected to be the order of 10 19 −10 20 cm -3 again comparable to that in a Nd:YAG plasma.…”
Section: Fig 6: Comparison Between a Discharge Produced Plasma (Dpp)mentioning
confidence: 93%
“…Hosokai et al have shown that the control of the injection vapor velocity by varying the ablating pulsed laser energy can improve the EUV emission efficiency. 12,13) However, the dynamics of laser-assisted discharge plasma is different from the one of conventional gas-fueled Z-pinch plasma. Study of the plasma dynamics will reveal the EUV source evolution during the laserassisted discharge.…”
Section: Introductionmentioning
confidence: 99%
“…Because a discharge can last for tens of microseconds, then the lifetime of the EUV plasma can be extended, 11,12 which should significantly increase the plasma efficiency and greatly expand the electrode lifetime.…”
mentioning
confidence: 99%